Surface finishing of glass ionomer - Paulillo, Luis Alexandre M. S.; Coradazzi, João L. [UNESP]; Lovadino, José R.; Serra, Mônica C. (My University, 1997)
Purpose: To evaluate the surface roughness and staining of a glass ionomer cement when subjected to different finishing procedures. Materials and Methods: Sixty-four discs of Chem-Fil II glass ionomer cement were submitted to staining test with methylene blue by spectrophotometry and roughness test by profilometry. Four groups were evaluated: Mylar matrix (control), Sof-Lex discs, Enhance points, and diamond bur. Results: Staining and roughness test, analyzed by ANOVA and Tukey's test, showed that the best surface was obtained when the material cured in contact with the Mylar matrix strip or when treated with Sof-Lex discs. The poorest results were obtained after using the diamond bur.
Keywords: aluminum oxide; ChemFil II; diamond; glass ionomer; analysis of variance; chemistry; comparative study; equipment design; evaluation; instrumentation; surface property; tooth brushing; Aluminum Oxide; Analysis of Variance; Dental Polishing; Diamond; Equipment Design; Evaluation Studies; Glass Ionomer Cements; Surface Properties